Analisis faktor-faktor yang mempengaruhi keputusan konsumen berbelanja di toko perlengkapan islami (studi pada toko cahaya berkah samarinda) (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Ikram Ashari. Analysis of Factors Affecting Consumer Decisions Shopping in Islamic Equipment Stores (Study at Samarinda Blessing Light Shop). This research was under the guidance of Mr. Zainal Ilmi as Advisor I and Mrs. Siti Maria as Counselor II.This study aims to determine the effect of Products on Decisions, to determine the effect of Prices on Consumer Decisions Shopping at Samarinda Blessing Light Shop.The method of data collection in this study uses a questionnaire with a Likert scale. The technique of determining the sample in this study was carried out using Accidental Sampling techniques. For this reason, the researchers took 100 consumers of Toko Cahaya Berkah Samarinda to be sampled in this study. The hypothesis test used in this study is Multiple Linear Regression using SPSS 23.0 Software.The results of this study indicate that Product has a positive and significant effect on consumers' decision to shop at Toko Cahaya Berkah Samarinda and Price has a positive and significant effect on consumer decisions to shop at Cahaya Berkah Samarinda Shop.